Theoretical Investigation on Elastic, Thermal and Ultrasonic Properties of Nanostructured HfN layers Growth on MgO (001) Substrate - Yadawa, Pramod Kumar; Srivastav, Prashant (Physics and Chemistry of Solid State, 2025)
In the current study, we used higher order elastic coefficients to compute the elastic, mechanical and thermo-physical characteristics of HfN/MgO (001) nanostructured materials at temperatures between 50 and 300 K. Two significant factors that are taken into consider when computing the second and third order elastic constants in this temperature(50K-300K) range are the nearest-neighbor distance and the hardness parameter. To evaluate the thermal and mechanical characteristics of the HfN/MgO (001) nanostructured layer, the analytical results of SOECs were employed to determine Young's modulus, thermal conductivity, Zener anisotropy, bulk modulus, thermal energy density, shear modulus, furthermore Poisson's ratio. Debye average velocity, hardness, melting temperature and ultrasonic Grüneisen parameters (UGPs) have been evaluated along different temperatures. The fracture/toughness (B/G) ratio in the current investigation is more than 1.75, signifying that the HfN/MgO (001) nanostructured layer is ductile in nature within this range of temperature. The selected materials fully satisfy the Born-mechanical stability requirement. It has been evaluated how long thermal relaxation takes to complete, how thermo-elastic relaxation attenuates ultrasonic waves, and how phonon-phonon interaction processes attenuate ultrasonic waves in this medium. The research results and other well-known physical characteristics are helpful for commercial applications.